PENEMUAN HUKUM OLEH HAKIM DALAM PERKARA WARIS SESUAI ASAS KEADILAN - Ning Adiasih (Departemen Hukum Perdata, 2018)
The living law is a reﬂ ection of the community values as accommodated in Article 5(1) of Law No. 48 of 2009 concerning Judiciary Power, which encourages judges to ﬁ nd and apprehend the values of law and justice of the societies. Inheritance dispute settlement in Indonesia may give the judges some options to implement certain law because of the pluralistic pattern of Indonesian inheritance law. On the other hand, the judges may have function to complement statutory laws and may create new law through forming law or ﬁ nding law to be implemented on certain pending case. The judges must have a thorough knowledge and interpret the law applied on certain case. For instance when the deceased was a Moslem, while one of the heirs is a non-Muslim, the judges of religious court may decide that non-Muslim heir entitled to the bequest as wasiat wajibah. Likewise, the judges of district court may implement inheritance law of adat law or Civil Code. The pluralism of the sources of law in inheritance cases is quite a problem for the judges, therefore the Supreme Court has enacted a guidelines in Circular Letter No. MA/Kumdil/171/VK/1991, dated on 8 May 1991. This article will question the implementation of the guidelines.